Mercury intrusion porosimetry in pulp and paper technology - Moura, M. J. (2005)
Mercury intrusion is frequently used for the characterization of porous materials, giving access to parameters such as porosity and pore size distribution as well as density (skeletal and bulk).The present work aims at studying the suitability of the mercury intrusion technique to evaluate the pore structure and related information of different kinds of woods used for pulp production, pulp handsheets and commercial paper sheets. Differences in wood structure, pulp composition and paper composition and structure could be easily detected by changes in the measured parameters, thus enabling a better understanding and/or prediction of the behaviour of these materials.